Sistema de refúgio no Brasil: uma reflexão sobre as políticas públicas específicas para refugiados - Sousa, Lívia Maria de (2017)
This paper aims to develop an analysis of public policies adopted in Brazil in favor of refugees as they contribute to the success of lasting solutions for repatriation, resettlement and local integration. At the internal level, the refuge system is structured in a normative framework that guarantees the exercise of refugee rights on equal terms with nationals. In addition, recognizing the specificity of the vulnerability of the victim of persecution and of graves and widespread violations of human rights, the refuge system guarantees specific rights for this group of migrants. As the focus of any protection regime is on the definition of who is subject to protection and on the definition of measures available for effective protection, we seek to develop the concept of refugee by differentiating it from other categories of forced migrants, protection rights that materialize in public policies. We seek to show that Brazil has an advanced protection system, insofar as it recognizes an equal non-exercise of rights between refugees and national non-abstract plan, with the Brazilian refuge system still presents difficulties of implementation and challenges. The methodology used in the research consists predominantly of a review of the bibliographical material in view of the controversies that the topic raises, as well as an analysis of the international normative framework on international refugee law, including treaties, protocols, principles and domestic legislation. UNHCR and CONARE database and specialized texts were also used as a research source, among other data available in international organizations and non-governmental entities with public access.